Islamic Politics on Forestry and Land Rehabilitation: A Case Study in Ulu Belu Tanggamus Lampung - Feliza, Amelia Resti; Yudha, Gesit; Qohar, Abdul (POLITEA, 2025)
Forest and Land Rehabilitation (FLR) is essential for maintaining ecological balance, particularly in Ulu Belu District, Tanggamus Regency, which faces a high risk of landslides. This study examines the strategies adopted by the Forestry Service in implementing forest and land rehabilitation efforts and the challenges encountered. A qualitative research approach was applied, using data collection methods such as observation, interviews, and documentation with relevant stakeholders, including the Forestry Service and the local community. Findings indicate that the Forestry Service has employed multiple strategies, including the Community Forestry Program (HKm), agroforestry practices, planting soil-stabilizing vegetation, and conducting public awareness campaigns on environmental conservation. However, these initiatives face significant hurdles, such as low public engagement, financial constraints, and the ongoing conversion of protected forests into farmland. Additionally, improper land management has further exacerbated landslide risks and environmental degradation. To improve the efficiency of rehabilitation programs, a more holistic approach is necessary. This includes offering incentives to farmers who implement conservation-oriented agricultural methods, strengthening institutional frameworks within social forestry programs, and promoting collaboration among the government, local communities, and private entities. By adopting more cohesive and sustainable strategies, forest and land rehabilitation in Ulu Belu District can effectively mitigate disaster risks and ensure long-term ecological stability for future generations.